Erratum to: Complete mitochondrial genomes of Thai and Lao populations indicate an ancient origin of Austroasiatic groups and demic diffusion in the spread of Tai–Kadai languages (Hum Genet, (2017), 136, (85-98), 10.1007/s00439-0z016-1742-y) - Kutanan W. (2017)
© 2017, Springer-Verlag Berlin Heidelberg. The author would like to correct the errors in the publication of the original article. The corrected details are given below for your reading. In the‘MtDNA sequencing and multiple alignment’ section, third sentence should read as: Several Illumina platforms and lengths of sequencing reads were employed, with post-processing using Illumina software and the Free Improved Base Identification System (freeIbis) (Renaud et al. 2013). The correct reference should be: ‘Renaud G, Kircher M, Stenzel U, Kelso J (2013) freeIbis: an efficient basecaller with calibrated quality scores for Illumina sequencers. Bioinformatics 29(9):1208–1209”.